KEPADATAN POPULASI KUTU DAUN (Myzus persicae) DAN PREDATORNYA (Monoshillus sexmaculata) PADA TANAMAN CABE (Capsicum annum) DI KECAMATAN KOTOPARIK GADANG DIATEH KABUPATEN SOLOK SELATAN - Dafrinal, Dafrinal; Widiana, Rina; Lusi, Armein (Pendidikan Biologi, 2013)
Chili is a herbaceous plant of the family eggplant (Solanaceae) which has the scientificname Capsicum annuum L. Chili has a lot of nutrients and vitamins, such as calories, protein, fat,carbohydrates, calcium, Vitamin A, Vitamin B1 and Vitamin C. Besides being used for domesticpurposes, peppers can also be used for industrial purposes such as, industry-seasoning, food andmedicine or herbal. Efforts to increase the production of chili still have problems due to pestaphids (Myzus persicae). Aphids reproduce in two ways: with and without marriage or their eggscan develop into young without fertilization (Partegonesis). This pests life cycle ranges from 7-10 days. These pests attack plants by sucking liquid chili leaves, shoots, flower stalks or otherplant parts, so that the leaves become mottled yellow (chlorotic) and eventually fall so chiliproduction declined. This insect will be clustered so as to cover part of the plant. Of control thispest than by using insecticides as well as biological control by predators. Predator beetles arefound is the javelin (Menochillus sexmaculata). Has done research on leaf Mite PopulationDensity (Myzus persicae) and the predatory beetle javelin (Menochillus sexmaculata) At Chilliplants. This study was conducted using a descriptive survey in April 2012, from the results, thepopulation density of aphids Myzus persicae with an average of 64.4 people per stick plantpredatory beetles and javelin Menochillus sexmaculata with an average of 2.4 individuals perstick plant.